# If one of the roots of ${x^2} + f\left( a \right)x + a = 0 $ is equal to the third power of the other for all real a, then

$a.{\text{ }}$ The domain of the real value function $f$ is the set of non-negative real numbers.

$

b.{\text{ }}f\left( x \right) = - {x^{\dfrac{1}{4}}}\left( {1 + {x^{\dfrac{1}{2}}}} \right) \\

c.{\text{ }}f\left( x \right) = - {x^{\dfrac{1}{4}}} + {x^{\dfrac{3}{2}}} \\

d.{\text{ None of these}} \\

$

Last updated date: 17th Mar 2023

•

Total views: 307.8k

•

Views today: 5.87k

Answer

Verified

307.8k+ views

Hint: - Use sum of the roots $ = \dfrac{{ - {\text{Coefficient of }}x}}{{{\text{Coefficient of }}{x^2}}}$, and product of roots $ = \dfrac{{{\text{constant term}}}}{{{\text{Coefficient of }}{x^2}}}$

Given quadratic equation ${x^2} + f\left( a \right)x + a = 0$

Let $\alpha $and $\beta $be the roots of the equation.

As you know sum of the roots $ = \dfrac{{ - {\text{Coefficient of }}x}}{{{\text{Coefficient of }}{x^2}}}$

And product of roots $ = \dfrac{{{\text{constant term}}}}{{{\text{Coefficient of }}{x^2}}}$

$

\Rightarrow \alpha + \beta = \dfrac{{ - f\left( a \right)}}{1} = - f\left( a \right).........\left( 1 \right), \\

\alpha \beta = \dfrac{a}{1} = a...............\left( 2 \right) \\

$

Now it is given that one root is the cube of other

$ \Rightarrow {\alpha ^3} = \beta $

From equation 2, considering real values of $\alpha $ we get

$

{\alpha ^3}\alpha = a \\

\Rightarrow {\alpha ^4} = a \\

\Rightarrow \alpha = \pm {a^{\dfrac{1}{4}}} \\

$

For positive value of $\alpha $

$ \Rightarrow \alpha = + {a^{\dfrac{1}{4}}}.............\left( 3 \right)$

Therefore from equation 1

$

\alpha + \beta = - f\left( a \right) \\

\Rightarrow \alpha + {\alpha ^3} = - f\left( a \right) \\

$

Now, from equation 3

\[

\Rightarrow {a^{\dfrac{1}{4}}} + {a^{\dfrac{3}{4}}} = - f\left( a \right) \\

\Rightarrow f\left( a \right) = - \left( {{a^{\dfrac{1}{4}}} + {a^{\dfrac{3}{4}}}} \right) \\

\Rightarrow f\left( a \right) = - {a^{\dfrac{1}{4}}}\left( {1 + {a^{\dfrac{1}{2}}}} \right) \\

\]

Now, in place of $a$ substitute $x$ in the above equation.

\[ \Rightarrow f\left( x \right) = - {x^{\dfrac{1}{4}}}\left( {1 + {x^{\dfrac{1}{2}}}} \right)\]

Hence, option (b) is correct.

Note: - In such types of questions the key concept we have to remember is that for a quadratic equation always remember the sum of roots and product of roots which is stated above, then simplify according to the given condition we will get the required answer.

Given quadratic equation ${x^2} + f\left( a \right)x + a = 0$

Let $\alpha $and $\beta $be the roots of the equation.

As you know sum of the roots $ = \dfrac{{ - {\text{Coefficient of }}x}}{{{\text{Coefficient of }}{x^2}}}$

And product of roots $ = \dfrac{{{\text{constant term}}}}{{{\text{Coefficient of }}{x^2}}}$

$

\Rightarrow \alpha + \beta = \dfrac{{ - f\left( a \right)}}{1} = - f\left( a \right).........\left( 1 \right), \\

\alpha \beta = \dfrac{a}{1} = a...............\left( 2 \right) \\

$

Now it is given that one root is the cube of other

$ \Rightarrow {\alpha ^3} = \beta $

From equation 2, considering real values of $\alpha $ we get

$

{\alpha ^3}\alpha = a \\

\Rightarrow {\alpha ^4} = a \\

\Rightarrow \alpha = \pm {a^{\dfrac{1}{4}}} \\

$

For positive value of $\alpha $

$ \Rightarrow \alpha = + {a^{\dfrac{1}{4}}}.............\left( 3 \right)$

Therefore from equation 1

$

\alpha + \beta = - f\left( a \right) \\

\Rightarrow \alpha + {\alpha ^3} = - f\left( a \right) \\

$

Now, from equation 3

\[

\Rightarrow {a^{\dfrac{1}{4}}} + {a^{\dfrac{3}{4}}} = - f\left( a \right) \\

\Rightarrow f\left( a \right) = - \left( {{a^{\dfrac{1}{4}}} + {a^{\dfrac{3}{4}}}} \right) \\

\Rightarrow f\left( a \right) = - {a^{\dfrac{1}{4}}}\left( {1 + {a^{\dfrac{1}{2}}}} \right) \\

\]

Now, in place of $a$ substitute $x$ in the above equation.

\[ \Rightarrow f\left( x \right) = - {x^{\dfrac{1}{4}}}\left( {1 + {x^{\dfrac{1}{2}}}} \right)\]

Hence, option (b) is correct.

Note: - In such types of questions the key concept we have to remember is that for a quadratic equation always remember the sum of roots and product of roots which is stated above, then simplify according to the given condition we will get the required answer.

Recently Updated Pages

If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE